Network segregation during episodic memory shows age-invariant relations with memory performance from 7 to 82 years - Grydeland, Håkon; Sneve, Markus H.; Roe, James M.; Raud, Liisa; Ness, Hedda T.; Folvik, Line; Amlien, Inge; Geier, Oliver M.; Sørensen, Øystein; Vidal-Piñeiro, Didac; Walhovd, Kristine B.; Fjell, Anders M. (Neurobiology of aging, 2025)
Lower episodic memory capability, as seen in development and aging compared with younger adulthood, may partly depend on lower brain network segregation. Here, our objective was twofold: (1) test this hypothesis using within- and between-network functional connectivity (FC) during episodic memory encoding and retrieval, in two independent samples (n = 734, age 7–82 years). (2) Assess associations with age and the ability to predict memory comparing task-general FC and memory-modulated FC. In a multiverse-inspired approach, we performed tests across multiple analytic choices. Results showed that relationships differed based on these analytic choices and were mainly present in the largest dataset,. Significant relationships indicated that (i) memory-modulated FC predicted memory performance and associated with memory in an age-invariant manner. (ii) In line with the so-called neural dedifferentiation view, task-general FC showed lower segregation with higher age in adults which was associated with worse memory performance. In development, although there were only weak signs of a neural differentiation, that is, gradually higher segregation with higher age, we observed similar lower segregation-worse memory relationships. This age-invariant relationships between FC and episodic memory suggest that network segregation is pivotal for memory across the healthy lifespan. •Within- and between network functional connectivity predict memory performance.•Multiverse-inspired analyses showed varying results depending on analytic choices.•Memory associations particularly in the largest dataset were age-invariant across the lifespan.•Dedifferentiation might be better characterized as degrees of differentiation.